(3TQM GdYhGed GdeFIs - (3fUMj OQhjT eMeO Hf eMeO GdESJGfHhdjs; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3hHYO, ajbhd GdYHO GdabjQ OQhjT eMeO Hf eMeO Hf eMeO(B: (3deG cGf cJGH GdYhGed GdeNJUQ dCUhd GdYhGed LGeYkG s
(3BNQgG (B:s
(3aGMaX eG ajg ef GdYhGFO hGdahGFO hbO hbY GdfghV ef GdShGO Edi GdHjGV Ydi jO eYQHg GdabjQ Edi Gddg fUMj OQhjT eMeO Hf eMeO Hf eMeO GdESJGfHhdj s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs